Effects of Age on Dual-Task Walking While Listening. Issue 4 (4th July 2019) - Nieborowska, Victoria; Lau, Sin-Tung; Campos, Jennifer; Pichora-Fuller, M. Kathleen; Novak, Alison; Li, Karen Z. H.
Abstract: This study examined the effects of age on single- and dual-task listening and walking during virtual street crossing. Seventeen younger and 12 older adults participated. In each listening trial, three sentences were presented simultaneously from separate locations. Participants were instructed to report the target sentence. Predictability of the target sentence location was varied. Treadmill walking was measured using motion analysis. Measures included word recognition accuracy, head and trunk angles, and spatiotemporal gait parameters. Older adults exhibited a more upright head alignment and less variability in stride time during dual-tasking, particularly under less certain target sentence location conditions. Younger adults' walking was unaffected by dual-task demands. Together, the results indicate greater postural prioritization in older adults than young.